Methods of cotton stalk destruction and survival of boll weevil - Ribeiro, Edenilson Batista; Castellani, Maria Aparecida; Silva, Carlos Alberto Domingues da; Melo, Thiago Lima; Silva, Gustavo dos Santos; Vale, Willian Santos do; Santos, Alexsandra Sousa (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the effectiveness of methods for the destruction of cotton (Gossypium hirsutum) stalks on the remainder population of cotton boll weevil (Anthonomus grandis). The experiment was carried out in a randomized complete block design with four replicates and five treatments: mowing and application of 2,4‑D and beta‑cyfluthrin; mowing and application of 2,4‑D and glyphosate; mowing and harrowing; mowing and application of 2,4‑D and beta‑cyfluthrin, besides harrowing; and a control without destruction. Boll weevil amount was determined after the destruction of cotton crop residues by counting the caught insects both in pheromone traps and within the dry bolls inside the cages and in the outer area. The average number of boll weevil adults captured in pheromone traps within the cages ranged from 0.71 to 1.35 individuals. The highest number of dry bolls and boll weevils from dry bolls, in and out of cages, was observed in the control. The lowest number of insects was observed in the treatments with harrowing and mowing and in those with mowing and harrowing with application of 2,4‑D and beta‑cyfluthrin, which are efficient in the reduction of dry bolls and boll weevil adults. All the evaluated methods reduce the amount of live boll weevils inside dry bolls.